Methods of assessing associated reactions of the upper limb in stroke and traumatic brain injury: A systematic review. (23rd February 2016) - Kahn, Michelle B.; Mentiplay, Benjamin F.; Clark, Ross A.; Bower, Kelly J.; Williams, Gavin
Abstract: Objective : To determine the assessment methods for upper limb (UL) associated reactions (ARs) in people with acquired brain injury (ABI). Methods : A systematic search of 10 databases was performed for Stage 1 to identify methods that quantify ARs of the hemiplegic UL. Stage 2 searched four databases to examine the clinimetric properties and clinical utility of these methods. Two independent reviewers identified relevant articles, extracted data, assessed study methodological quality and rated the clinimetric properties and clinical utility. Results : Eighteen articles were included. The methods used to evaluate ARs were surface electromyography (11), goniometry (5), dynamometry (5), electrogoniometry (1), subjective clinician (2) and patient rating forms (2). Electromyography, electrogoniometry and dynamometry implemented stationary, seated positions using maximal voluntary contractions of the less impaired UL as the provocative task. Standard goniometry most frequently tested ARs dynamically, using a mobility task to provoke the AR. There was limited clinimetric data available. Only half of the assessment methods were deemed clinically feasible. The most common methods were laboratory-based. Conclusion : There were a limited number of methods used to assess ARs in people with ABI and the measurement properties of these outcomes were largely unreported. No gold standard was identified.